ISTIFHAM SEBAGAI METODE DAKWAH AL-QURAN - Mira Fauziah (Kalam: Jurnal Agama dan Sosial Humaniora, 2017)
Da'wah is an obligation that must be carried out by Muslims, who essentially work to prevent indecency and great evil and suggest the good deeds. The Quran itself is a primary source of command to do Da'wah and al-Quran also shows various methods of propagation that can be done. This paper examines the istifham contained in the Quran as a method of Dawah. Verses of the Quran containing istifham are spread across a number of the surah. Of the 114 surah al-Quran, the most widely known to contain istifham is surah ar-Rahman totaled 31 verses and surah al-Mursalat as 6 verses. The author examines both of these Surahs to figure out a method of Dawah contained therein. The results of this Istifham is the author of the analysis methods of da'wah al-Quran is the perfect posed to mankind, with the hope of human beings can ponder and realize the truth conveyed by Allah swt in the Quran.